Esterification of oleic acid with alcohols over Cu-MMT K10 and Fe-MMT K10 as acid catalysts - Farah Wahida Harun; Jihadi N.I.M.; Ramli S.; Hassan N.R.A.; Zubir N.A.M. (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS